Development of Powered Disk Type Sugar Cane Stubble Saver - Radite P.A.S; I Nengah Suastawa (Jurnal Keteknikan Pertanian, 2009)
The objective of this research was to design, fabricate and test a prototype of sugar cane stubble saver based on powered disk mechanism. In this research, a heavy duty disk plow or disk harrow was used as a rotating knife to cut the sugarcane stubble. The parabolic disk was chosen because it is proven reliable as soil working tools and it is available in the market as spare part of disk plow or disk harrow unit. The prototype was mounted on the four wheel tractor’s three point hitch, and powered by PTO of the tractor. Two kinds of disks were used in these experiments, those were disk with regular edge or plain disk and disk with scalloped edge or scalloped disk. Both disks had diameter of 28 inch. Results of field test showed that powered disk mechanism could satisfy cut sugar cane’s stubble. However, scalloped disk type gave smoother stubble cuts compared to that of plain disk. Plain disk type gave broken stubble cut. Higher rotation (1000 rpm) resulted better cuts as compared to lower rotation (500 rpm) both either on plain disk and scalloped disk. The developed prototype could work below the soil surface at depth of 5 to 10 cm. With tilt angle setting 20O and disk angle 45O the width of cut was about 25 cm.Keywords: sugar cane, stubble shaver, powered diskDiterima: 4 Nopember 2008; Disetujui: 11 Maret 2009